Deep NIR imaging of galaxy clusters in the Vela supercluster - Hatamkhani, Narges (Department of Astronomy, 2023)
Gravitational forces of large galaxy over densities can perturb the smooth motions expected from the expanding universe, causing peculiar motions. The observed Cosmic Microwave Background (CMB) dipole is the result of the Local Group's peculiar motion, the direction and amplitude of which are still not fully resolved. The newly discovered Vela Supercluster (VSCL, ` = 272. ◦5±20◦ , b = 0◦±10◦ ), an extended structure behind the Zone of Avoidance (ZoA) at cz ∼ 18000 km s−1 , may be a not insignificant contributor to the residual bulk flow that arises beyond cz ∼ 16000 km s−1 . Knowledge of the structure and richness of galaxy clusters within the VSCL will enable us to assess the morphology and mass of this partially obscured supercluster. Compared to the shorter optical wavelengths, near infrared (NIR) observations are less affected by dust obscuration in the ZoA and therewith offer a better tool to probe galaxy clusters in the VSCL, and get a better understanding of this extended supercluster. A series of deep NIR observations of prospective clusters identified in the VSCL were conducted in the J, H and Ks bands with the InfraRed Survey Facility (IRSF) telescope. For 6 (VC02, VC04, VC05, VC08, VC10 and VC11) out of 20 potential clusters a complete set of science quality images were obtained (out to ∼ 70% of the Abell radius) and were fully reduced. I identified galaxy candidates in each cluster using the Source Extractor software, validated them through visual inspection of the RGB composite images and created a catalogue of galaxies with their astrometric and photometric parameters using the IRSF pipeline. There are a total number of 1715 identified galaxies distributed over the six clusters, of which only ∼ 15% were previously known. Investigating the effect of foreground extinction in the region of the observed clusters shows that, the VC02 cluster has the highest foreground extinction while VC04 and VC05 have the lowest (hAKsi = 0. m10, hAKsi = 0. m07 and hAKsi = 0. m06 respectively). I show that the effect of extinction on the isophotal magnitudes is small compared to the foreground extinction and additional extinction-correction is not required. The extinction-corrected completeness magnitude limit for this survey is Mo Ks < −21. m5 which is ∼ 2. m0 deeper than 2MASX. The six observed clusters were analysed in detail out to the cluster centric completeness radius of rc < 1.5 Mpc and Mo Ks < −21. m5. Comparison of the iso-density contour maps and radial density profiles of the VSCL clusters with Ks-band data of well-known clusters (Coma, Norma, 3C129 and Virgo), finds VC04 to be a regular and massive cluster comparable to Coma and Norma (although its velocity dispersion seems rather low for a rich cluster); it is the richest of the six. H I analysis (using MeerKAT-16 data) shows that the spiral galaxies in VC04 are severely H I deficient which is consistent with its richness. VC02 and VC05 are found to be relatively rich clusters while VC08 is rather poor. VC10 has a filament-like structure and is not a cluster. VC11 is an intermediate cluster which contains two major subclusters. It appears that many of the VSCL clusters (VC02, VC04, VC05 and VC11) are not relaxed yet and are still evolving. The Ks-band Luminosity Function (LF) was derived for the VSCL clusters up to Mo Ks < −21. m5 (∼ 2. m5 deeper than M∗ ). I demonstrate that the Red-Sequence (RS) method is a reliable method to measure the LFs of the clusters and then compute the Ks-band LFs of the Coma, Norma and Virgo clusters using the RS method to compare to the LFs of the VSCL clusters. The comparisons show that M∗ derived for the LF of VC04 (M∗ = −24. m70 ± 0.42) agrees well with those of other local clusters. The bright end of the VC04 LF is compatible with that of massive clusters that are dominated by early-type galaxies such as Norma, while the slope (α = −0.89±0.13) is shallower compared to those of younger clusters. The analysis of this to date small sample of the VSCL clusters (6 out of at least 20) shows that the VSCL contains potentially many more rich clusters indicative of it being a rich supercluster.